Narrating flight and asylum - Beck, Mandy; Gualtieri, Claudia 1956-; Pedretti, Roberto; Sandten, Cecile 1966- (WVT Wissenschaftlicher Verlag Trier, 2022)
Over the past several decades, migration, displacement and asylum-seeking have become constitutive elements of contemporary conjuncture, generating conditions that are often described as "crises". Since the beginning of what has commonly been referred to as the refugee crisis of 2015, there have been discussions within political, social, media and online contexts about European nation-states closing their borders to asylum seekers and refugees. More often than not, these discussions are accompanied by racism, xenophobia or profound fears. To help mitigate these negative effects, the essays in this volume on NARRATING FLIGHT AND ASYLUM focus on the question of how flight and asylum-seeking are narrated in in-depth analyses of literary and media texts, political and legal contexts, and museum work. More generally, they try to explore opportunities for political intervention and ethical commitment within a European, and specifically Italian-German-British, framework. With this volume, the intention is to focus on the issues of 'making voices heard' and 'making people on the margins seen' in a Europe where it is possible to observe what might be called "a war on immigration." The volume is inter- and cross-disciplinary, aimed at building a conversation that will expand inside and outside of academia, to include diverse, non-canonical cultural voices and methodological approaches and thus explore the topic of refugeeism and asylum-seeking across Europe and beyond.
Aus der Introduction: leading to the one-day conference "Narrating Flight and Asylum", which took place on 6 November 2020. This collection primarly consists of contributions to that conference.
Keywords: Italienisch; Flucht -- Motiv; Comic; Film; Englisch; Literatur; Deutsch; Asyl -- Motiv; Konferenzschrift -- 06.11.2020 -- Online